An emerging role for adenosine and its receptors in bone homeostasis - Evans, Bronwen; Ham, Jack (Frontiers in Endocrinology, 2012)
Bone is continually being remodeled and defects in the processes involved lead to bone diseases. Many regulatory factors are known to influence remodeling but other mechanisms, hitherto unknown, may also be involved. Importantly, our understanding of these currently unknown mechanisms may lead to important new therapies for bone disease. It is accepted that purinergic signaling is involved in bone, and our knowledge of this area has increased significantly over the last 15 years, although most of the published work has studied the role of ATP and other signaling molecules via the P2 family of purinergic receptors. During the last few years, however, there has been increased interest within the bone field in the role of P1 receptors where adenosine is the primary signaling molecule. This review will bring together the current information available in relation to this expanding area of research.